Modification of Sourdough Using Snake Fruit Starter - Fiorellino, Kenneth; Billy Tanius; Ni Ketut Veri Kusumaningrum (INSPIRE : Journal of Culinary, Hospitality, Digital & Creative Arts and Event, 2024)
This research investigated the use of snake fruit (Salacca zalacca) as a sourdough starter, aimed at promoting the utilization of snake fruit in culinary products and understanding feedback from respondents based on the resulting product. With the rising popularity of sourdough bread and the growing demand for locally sourced ingredients, exploring unconventional starter cultures has become essential. The study is conducted through research and development by evaluating the properties of 3 types of snake fruit namely” Pondoh, Gading, and Gula Pasir”. Acidity, carbohydrate content, and sugar levels are used to determine its compatibility through sourdough fermentation. A comprehensive comparison is conducted between the resulting product and the widespread yeast-based sourdough bread. Interviews and questionnaires were distributed to the public and culinary professionals to extract information. A total of 25 individuals has generally positive feedback with the results of the “Pondoh and Gading” variety, showing likeness towards texture and crust. The remaining subject “Gula Pasir” was deemed to be incompatible for sourdough production due to its low acidity. The findings of this study hold promise to the Indonesian culinary industry by capitalizing on the diverse range of tropical fruits to expand and incorporate sustainable local ingredients. Embracing snake fruit as a sourdough starter presents a lucrative prospect for promoting local gastronomic diversity.